Genomic surveillance of sars-cov-2 in malaysia during the era of endemic covid-19 - Tze, Yan Lee; Wai, Feng Lim; Geik, Yong Ang; Choo, Yee Yu (Multidisciplinary Digital Publishing Institute, 2023)
On 5 May 2023, WHO declared the end of coronavirus disease 2019 (COVID-19) as a public health emergency of international concern. However, the risk of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants causing rapid and high surges in cases and deaths remained. In Malaysia, five COVID-19 waves during the pandemic phase were well characterized, but similar studies focusing on the endemic phase were lacking. Hence, we retrieved 14,965 SARS-CoV-2 genomic sequences from the GISAID EpiCoV database for clade, lineage, and phylogenetic analysis in order to provide an insight into the population dynamics of SARS-CoV-2 that circulated in Malaysia from June 2022 to April 2023. The dominance of the Omicron variants was observed, and two new waves of infections driven by BA.5.2 and XBB.1, respectively, were detected. Data as of April 2023 also pointed to a possible eighth wave driven by XBB.1.9. Although new variants associated with higher transmissibility were behind the multiple surges, these subsequent waves had lower intensities as compared to the fourth and fifth waves. The on-going circulation and evolution of SARS-CoV-2 mean that COVID-19 still poses a serious threat, necessitating active genomic surveillance for early warning of potential new variants of concern.